THE INVISIBLE MAN - Wells, H. G., 1866-1946; Bullard, Nick; Shephard, David; Pitts, Sorrel (London : Penguin Books, 2021)
Griffin is a scientist, and he discovers how to make things invisible. Then he becomes invisible himself. Griffin thinks that an invisible man will have a lot of power. But life becomes more and more difficult." -- back cover
Includes questions and excercises
Keywords: Scientists -- Juvenile fiction